Analisis Pengaruh Budaya Organisasi, Komitmen Afektif, Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Motivasi Sebagai Variabel Mediasi (Studi Kasus Pada Pusat Oleh-Oleh Jogja Pasaraya Dan Batik Adikusumo Malioboro) - Vinda, Galuh Gian; Welsa, Henny; Kirana, Kusuma Candra (Universitas Muhammadiyah Metro, 2023)
This study aims to analyze the relationship between organizational culture, affective commitment, work environment on employee performance with motivation as an intervening variable. This research method uses descriptive quantitative by using primary data obtained from distributing questionnaires. In this study, using the census technique, where all populations are taken, each population has the same opportunity to be sampled. The number of samples taken in this study were 90 questionnaires. Data were analyzed using SPSS and Smart PLS. The results showed that organizational culture had a positive and significant effect on motivation with a significance level of 0.000 <0.05, so hypothesis I was accepted. Affective commitment has a positive and significant effect on motivation with a significance level of 0.030 <0.05, so hypothesis II is accepted. The work environment has no positive and significant effect on employee performance with a significance level of 0.093 > 0.05, so hypothesis III is rejected. Motivation has no positive and significant effect on employee performance with a significance level of 0.379 > 0.05, so hypothesis IV is rejected. Organizational culture has a positive and significant effect on employee performance with a significance level of 0.000 <0.05 (p<0.05), so hypothesis V is accepted. affective commitment has no positive and significant effect with a significance level of 0.081 > 0.05, so the hypothesis in VI is rejected. The work environment has no positive and significant effect on employee performance with a significance level of 0.676 > 0.05, so hypothesis VII is rejected. Organizational culture on employee performance with motivation as an intervening variable with a significance level of Z score 0.83 < 1.96, then hypothesis VIII is rejected. Affective commitment to employee performance with motivation as an intervening variable with a significance level of Z score 0.57> 1.96 then hypothesis IX is rejected. Work environment on employee performance with motivation as an intervening variable with a significance level of Z score 0.69> 1.96 then hypothesis X is rejected.